Sifat Fisik dan Mekanik Kayu Bisbul (Diospyros blancoi A.DC.) The Physical and Mechanical Properties of Bisbul Wood (Diospyros blancoi A.DC.) - Abdurachman Abdurachman (Masyarakat Peneliti Kayu Indonesia, 2009)
Bisbul (Diospyros blancoi A.DC.) signifies as one of the wood species that belong to the streaked Ebony. InIndonesia, this species prevalently grows in Sumatera andWest Java. The branch-free stem of this species when reaching over 25 years can reach about 5 m in height and 30 cm in diameter. It is categorized as dense wood with dark color, which gradually appears like Eben wood. This wood usually finds much uses as handcraft and merchant items.This research aimed to look into characteristic and uses of Bisbul wood through laboratory-scale testing on its physical and mechanical properties. This examined wood species was originated from the community-owned forest situated inBogorregency. The wood samples were taken from three height positions at branch-free Bisbul tree stems (i.e. top, middle, and butt portions) and from three lateral portions (sapwood, heartwood, and pitch), and then prepared to specimens measuring 2 cm by 2 cm in cross-section area. Each of the combination between such height and lateral-depth positions was replicated three times. The tested physical and mechanical properties covered specific gravity, moisture content, shrinkage, static bending, compressive strength parallel to the grain, shear, tensile parallel to the grain, and impact bending.Results revealed that based on moisture content and specific gravity, Bisbul wood belongs to medium density and floats on the water. Its radial (R) and tangential (T) shrinkages were categorized as medium in the range of 0.92 2.74% and 2.26 4.04%, respectively with T/R ratio somewhat less than 2, indicating that the wood was unstable due to moisture changes. Air-dry moisture content at various height and depth positions ranged about 14 16%, but the density decreased moving from the top, middle, to butt portions. The density at top, middle, and butt portions was consecutively 0.756 0.806 g/cm3, 0.710 0.805 g/cm3, and 0.672 0.716 g/cm3. Based on the examined mechanical properties, Bisbul wood belonged to strength class II I at the butt and middle portion, and to class III II to top portion